Immanuel Kant and Endogenous Growth Theory. (25th September 2015) - Fagan, Gabriel; Gaspar, Vitor; McAdam, Peter
Abstract: Despite the modern origins of endogenous growth theory, we argue that the 'Idea for a Universal History with a Cosmopolitan Aim' written by Immanuel Kant in 1784 provides an early and coherent example of such a theory. Kant's endogenous growth mechanism is driven by the inherent rivalry that exists between agents which increases effort and strengthens the accumulation of knowledge, which in turn is carried through generations. In an exercise in 'rational reconstruction', we present a mathematical model of Kant's mechanism. We use the model to contribute to the contemporary policy debate as to whether 'keeping up with the Joneses' leads to excessive effort.